Prevalence of Internet gaming disorder and its association with psychiatric comorbidities among a sample of adults in three Arab countries - Tourki Abdulmhsen Almutairi; Khaled Sultan Almutairi; Khaled Mohamed Ragab; Anas Zakarya Nourelden; Ahmed Assar; Sajeda Matar; Hivan Haji Rashid; Mohamed Elsayed; Ahmed Hashem Fathallah; Manfred Spitzer; Carlos Schönfeldt-Lecuona; Collaboration Team (Middle East Current Psychiatry, 2023)
Abstract Background As Internet gaming became publicly available over the past 25 years, Internet gaming disorder emerged as a new diagnostic entity and became established in psychiatric diagnostic systems as a form of addiction. Given the recency of its advent, reliable data on the epidemiology and psychiatric comorbidity of this disorder in specific geographic regions are scarce and dearly needed for appropriate treatment. Results A total sample of number = 1332 participants completed the questionnaire. Four-hundred twenty-three of them were gamers; in this cohort, the prevalence of Internet gaming disorder was 6.1%. A strong association between Internet gaming and several psychiatric disorders (attention deficit, hyperactivity, depression, and anxiety) was found. Conclusions Internet gaming disorder is frequent in adults from Arab countries. It is associated with psychiatric comorbidities in this current sample; the nature of this association needs to be properly investigated.